Power allocation satisfying user fairness for integrated sensing and communication system based on orthogonal time frequency space modulation - Ke XU; Luping XIANG; Jie HU; Kun YANG (Dianxin kexue)
By sharing resources for radar sensing and communications, integrated sensing and communication (ISAC) has promising applications in diverse scenarios, such as human-machine interface, vehicle-to-everything (V2X), remote sensing, and environment surveillance.In order to resolve the frequency resource conflict in high-speed V2X networks, based on the modulation orthogonal time frequency (OTFS), the OTFS-ISAC system was proposed, where the base station receives reflected echoes to obtain sensing parameters of vehicle motion and then establish the vehicle’s mobile topology.Additionally, in terms of the multi-vehicle network, the design of OTFS-ISAC with NOMAsatisfying the fairness and the algorithm of power allocation were proposed.Simulations show that compared with the NOMA without radar sensing system, the proposed design improves the system data rate by 25%.